Graph coloring Sistem Pendaftaran dan Proses Penjadwalan Data Instruktur Berbasis Web dengan Algoritma Welch-powell - Sopiyan, Muhamad; Fauziah, Fauziah; Gunaryati, Aris; Fitri, Iskandar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Many things in this world are implementations of graph coloring, because the models are very useful for broad applications, such as registration and scheduling of web-based instructor data. The purpose of this study is to support the virtual training process by generating training schedules automatically. of the week. There are types of training programs with a duration of 1 hour, 2 hours and 3 hours. Previously the instructor had to register in advance and determine how many hours of training sessions and the availability of an empty schedule. The application of graph coloring can help formulate instructor schedules so that they do not clash with other instructors' schedules. From the results of this study, each instructor who teaches in a week is selected by the system with the total number of time slots in a week is 8x6 = 48 hours. If the total teaching hours of applicants reach 60, 61 or 62 hours, the system will shut down automatically.